A castor oil-containing dental luting agent: effects of cyclic loading and storage time on flexural strength - DERCELI, Juliana dos Reis; FAIS, Laiza Maria Grassi; PINELLI, Lígia Antunes Pereira (Journal of Applied Oral Science, 2014)
Favorable results in the use of castor oil polyurethane (COP) as pulp capping, membrane material, sealer, mouthwash and in bone repair, associated with the fact that Ricinus communis is not derived from petroleum and it is abundant in Brazil, encourage researches in the development of luting agents. Objectives This study compared the flexural strength (FS) of a castor oil-containing dental luting agent with a weight percentage of 10% (wt%) of calcium carbonate (COP10) with RelyX ARC (RX) after mechanical cycling (MC) and distilled water storage. Material and Methods Sixty-four specimens (25x2x2 mm) were fabricated and divided into two groups, COP10 and RX (control). Each group was divided into 4 subgroups (n=8) according to the storage time, 24 hours (24 h) or 60 days (60 d), and the performance (MC+FS) or not (only FS) of the mechanical cycling test. The FS (10 kN; 0.5 mm/min) and MC tests (10,000 cycles, 5 Hz, 0.5 mm/min) were carried out using an MTS-810 machine. The data were analyzed using ANOVA (α=0.05). Results The obtained FS (MPa) values were: COP10 24h- 19.04±2.41; COP10 60d- 17.92±3.54; RX 24h- 75.19±3.43; RX 60d- 88.77±6.89. All the RX specimens submitted to MC fractured, while the values for COP10 after MC were as follows: COP10 24h- 17.90±1.87 and COP10 60d- 18.60±1.60. Conclusions A castor oil-containing dental luting agent with a weight percentage of 10% (wt%) of calcium carbonate is resistant to mechanical cycling without decreases in flexural strength. However, mean COP10 showed only about 25% of the RelyX ARC mean flexural strength.